Application of Foam Glass-Ceramic Composite Thermal Insulation Material in Traditional Buildings - Qi Yu (Journal of Chemistry)
In order to solve the application of thermal insulation materials in traditional buildings, a foam glass-ceramic composite thermal insulation material was proposed for the application of traditional buildings. First, the preparation of the hydrated glass matrix was completed by using the colloidal chemical method with sodium water glass, boric acid, calcium bentonite, and fly ash as the main raw materials. Second, using the introduction of crystalline mineral powder fly ash and secondary heat treatment, a low-temperature foam glass-ceramic composite material with lightweight, high strength, good water resistance, and low cost is prepared. Finally, the process parameters such as dehydroxylation heat treatment temperature and holding time involved in the preparation process were explored and optimized. It is proved that the external content of fly ash is 20 wt.% and above, and the external content of boric acid is 1-2 wt.%. The mixed sol has a bulk density of 192–256 kg/m2, a compressive strength of 0.44–0.63 MPa, a weight loss rate of 5.1–7.8 wt%, and a softening coefficient of 0.85–0.95, and thermal conductivity is 0.056–0.064 W/(m·K).